Chromatin run-on and sequencing maps the transcriptional regulatory landscape of glioblastoma multiforme. (November 2018) - Chu, Tinyi; Rice, Edward; Booth, Gregory; Salamanca, H.; Wang, Zhong; Core, Leighton; Longo, Sharon; Corona, Robert; Chin, Lawrence; Lis, John; Kwak, Hojoong; Danko, Charles
Abstract The human genome encodes a variety of poorly understood RNA species that remain challenging to identify using existing genomic tools. We developed chromatin run-on and sequencing (ChRO-seq) to map the location of RNA polymerase for almost any input sample, including samples with degraded RNA that are intractable to RNA sequencing. We used ChRO-seq to map nascent transcription in primary human glioblastoma (GBM) brain tumors. Enhancers identified in primary GBMs resemble open chromatin in the normal human brain. Rare enhancers that are activated in malignant tissue drive regulatory programs similar to the developing nervous system. We identified enhancers that regulate groups of genes that are characteristic of each known GBM subtype and transcription factors that drive them. Finally we discovered a core group of transcription factors that control the expression of genes associated with clinical outcomes. This study characterizes the transcriptional landscape of GBM and introduces ChRO-seq as a method to map regulatory programs that contribute to complex diseases. Chromatin run-on and sequencing (ChRO-seq) is a new method that maps the location of RNA polymerase using virtually any input sample. Here, ChRO-seq is used to study nascent transcription in human glioblastoma, and to identify regulators of tumor subtype.